Social Norms and Female Labour Force Participation in Bangladesh: The Role of Social Expectations and Reference Networks. - Bellani, Luna; Biswas, Kumar; Fehrler, Sebastian; Marx, Paul; Sabarwal, Shwetlena; Al-Zayed Josh, Syed Rashed (Journal of Development Studies, 2026)
A large proportion of Bangladesh's working age female youth population is not in employment, education or training (NEET). Reducing this figure is an important policy objective. However, there is a broad consensus that pervasive gender norms in Bangladesh and other countries in the Global South hinder this goal. This study analyses the social basis of support for young working women. It departs from a theoretical understanding of norms as contingent on the expectations of one's reference network. Using vignette experiments, we show that manipulating others' expectations about the acceptability of female employment influences personal support for women entering the workforce. We also address the question of whose views matter. Manipulating the expectation that fathers (or husbands in the case of married NEETs) will support their daughters' (wives') employment has a particularly strong effect on respondents' support. In contrast, the attitudes of religious authorities and peers are surprisingly of little relevance. Our evidence suggests that (expectations of) traditional views of fathers and husbands on the role of women are a key obstacle to greater participation of young women in the labour force in Bangladesh.